Research supporting restoration aiming to make a fragmented landscape 'functional' for native wildlife. (30th December 2021) - Jones, Menna E.; Bain, Glen C.; Hamer, Rowena P.; Proft, Kirstin M.; Gardiner, Riana Z.; Dixon, Kirsty J.; Kittipalawattanapol, Kawinwit; Zepeda de Alba, Ana L.; Ranyard, Claire E.; Munks, Sarah A.; Barmuta, Leon A.; Burridge, Christopher P.; et al.
Summary: Temperate woodlands are amongst the most threatened ecosystems in Australia because the land on which they occur is highly suited to agriculture. Two hundred years of habitat loss and fragmentation in the Midlands agricultural region in Tasmania have led to widespread declines in native vertebrates and landscapes with populations of predators including feral Cat ( Felis catus ) and the native‐invasive Noisy Miner ( Manorina melanocephala ). Ecologists at the University of Tasmania co‐designed mechanistic animal‐centric research on mammals and birds in the Midlands to inform vegetation restoration carried out by Greening Australia that would support the recovery of wildlife species. We used species‐appropriate technologies to assess the decisions made by individual animals to find food and shelter and to disperse across this fragmented landscape, and linked these, together with patterns of occupancy, across multiple spatial and temporal scales. We focussed on a native (Spotted‐tailed Quoll, Dasyurus maculatus ) and an invasive (feral Cat, Felis catus ) carnivore, a woodland‐specialist herbivore (Eastern Bettong, Bettongia gaimardi ) and woodland birds including the native‐invasive Noisy Miner. Our results, which show intense predatory and competitive pressure of cats and populations of Noisy Miner on native fauna, highlight how grounding restoration in the context of ecological interactions is essential to success in managing the impacts of invasive species in restored landscapes. Successful restoration will require innovative approaches in plantings and field experimentation with artificial refuges, to reduce habitat suitability for the Noisy Miner and cats and provide refuges for native mammals and birds to live in the landscape where cats also occur. Our results emphasise the significance of structural complexity of restoration plantings for supporting the recolonisation and persistence of native fauna. At large landscape‐scale, we demonstrate the importance of retaining small habitat elements, including ancient paddock trees, pivot irrigation corners and small, degraded remnants, in facilitating occupancy and dispersal and, therefore, persistence of wild animals across this agricultural region.